The Implementation Of Character Education For Students In Learning Activities - Latifah Latifah; Lailatu Fitri; Nadirah Salsabila; Akhmad Kanzul Fikri (SCHOOLAR: Social and Literature Study in Education, 2023)
Education in this era of globalization not only teaches children to be intellectually intelligent but also spiritually intelligent. Basically, to face the global era or the development of the times as it is today, people who have good moral values are needed. Therefore, these moral values can be taught through education in the learning process. In the learning process, character education can be applied to form character and noble morals in students as a whole and integrated, as well as systematically in order to create people who have a good character spirit and are not only smart in terms of knowledge but also smart in terms of morals. Therefore, the researchers conducted observations with descriptive qualitative research using the survey method. In this research, the researchers went directly to the field to seek information and observations to find data. The research was conducted using the observation method directly on Islamic Junior high school ITMA Al-Aqobah 4 class 8 B students to collect data on character education that has been applied at school to students. Apart from observation, the researchers also conducted interviews with the principal and homeroom teacher. From the results of interviews through the principal of Islamic Junior high school ITMA Al-Aqobah 4, they have made various efforts to carry out character education in students. From the results of direct observation in the school environment, students have carried out the applied character education, although some have not implemented character education. From the checklist results, the average character assessment of students in class VIII B is 82.17%. The average character results show that students have very good criteria. So that the results of the character assessment show that most students have implemented character education. da hasil rata-rata karakter menunjukkan bahwa siswa memiliki kriteria yang sangat bagus. Sehingga hasil penilaian karakter menunjukkan sebagian besar siswa sudah menerapkan pendidikan karakter.